Self-contained, tetracycline-regulated retroviral vector system for gene delivery to mammalian cells - Werner Paulus; Inge Baur; Frederick M. Boyce; Xandra O. Breakefield; Steven A. Reeves (1996)
Retroviral vectors that contain the tetracycline-inducible (Tet) system were developed. The two components of the Tet system were organized within the vectors in a manner that stringently maintains tetracycline-dependent regulation. Regulated expression of an indicator gene inserted into the retroviral vectors was examined in several different cell types. In infected NIH 3T3 cells, levels of induction in the absence of tetracycline were observed to be as much as 336-fold higher than levels in the presence of tetracycline, which were extremely low. Tetracycline-dependent regulation was observed in all other transduced cell types and ranged from 24- to 127-fold. The generation of retroviral vectors containing regulatory elements that allow for the regulated expression of heterologous genes and that have the ability to infect virtually all dividing target cells should greatly facilitate the biochemical and genetic examination of a broad range of genes. Moreover, these inducible retroviral vectors should prove useful in gene therapy applications.